2014
DOI: 10.1016/j.gpb.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Association Between rs1344706 of ZNF804A and Schizophrenia: A Meta-Analysis

Abstract: Schizophrenia is one of the most serious mental diseases found in humans. Previous studies indicated that the single nucleotide polymorphism (SNP) rs1344706 in the gene ZNF804A encoding zinc finger protein 804A was associated with schizophrenia in Caucasian population but not in Chinese Han population. However, current results are conflicting in Asian population. In the present study, a meta-analysis was performed to revisit the association between rs1344706 and the risk of schizophrenia in Asian, Caucasian an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
(33 reference statements)
2
9
0
Order By: Relevance
“…gene (Ferreira et al 2008;Green et al 2010;Guan et al 2014;He et al 2014;Jiang et al 2015;Nyegaard et al 2010;Sklar et al 2008;Zheng et al 2014) and allele A of the rs1344706 SNP of the ZNF804A gene (Donohoe et al 2010;Sun et al 2015;Zhang et al 2015;Zhu et al 2014). The latter variant has been associated with white matter (WM) microstructural abnormalities as we report elsewhere (Mallas et al 2016).…”
Section: Genome-wide Studies Have Identified Allele a (Adenine)supporting
confidence: 52%
See 1 more Smart Citation
“…gene (Ferreira et al 2008;Green et al 2010;Guan et al 2014;He et al 2014;Jiang et al 2015;Nyegaard et al 2010;Sklar et al 2008;Zheng et al 2014) and allele A of the rs1344706 SNP of the ZNF804A gene (Donohoe et al 2010;Sun et al 2015;Zhang et al 2015;Zhu et al 2014). The latter variant has been associated with white matter (WM) microstructural abnormalities as we report elsewhere (Mallas et al 2016).…”
Section: Genome-wide Studies Have Identified Allele a (Adenine)supporting
confidence: 52%
“…Genome‐wide association studies (GWAS) have identified two genetic variants conferring, so far the most reproducible, risk for both SZ and BD: allele A of the single nucleotide polymorphism (SNP) labelled rs1006737 of the CACNA1C gene (Ferreira et al ; Green et al ; Guan et al ; He et al ; Jiang et al ; Nyegaard et al ; Sklar et al ; Zheng et al ) and allele A of the rs1344706 SNP of the ZNF804A gene (Donohoe et al ; Sun et al ; Zhang et al ; Zhu et al ). The latter variant has been associated with white matter (WM) microstructural abnormalities as we report elsewhere (Mallas et al ).…”
mentioning
confidence: 99%
“…They are involved in multiple functions, including transcriptional activation, protein folding, RNA packaging, lipid binding, and DNA recognition (Laity et al, 2001). Recently, focus has been given to specific SNPs of ZNF804A (e.g., rs1344706, rs4667001, and rs728534) with a meta-analysis by Zhu et al (2014) showing an association with schizophrenia risk in both Asian and Caucasian populations. When investigating these SNPs in reference to schizotypy, we see mixed results with some studies finding a significant association with schizotypy (Yasuda et al, 2011; Stefanis et al, 2013) and others not (Leach et al, 2013).…”
Section: Schizotypal Trait Genes: Association Studies (Schizotypy Scmentioning
confidence: 99%
“…To this end, meta-analysis tests are performed to revalidate existing hypotheses using newer GWAS datasets. The association of this SNP has been inspected by four previous meta-analyses, 10 , 11 , 32 , 33 with the first study consisting of 12 studies from the Chinese population and stating no association and the second study consisting of 13 studies from the Asian population and stating the presence of association. The third meta-analysis consisted of 30 studies, which included Asians, Caucasians and Americans.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, performing further analysis, they detected that the SNP rs359895 has an association with schizophrenia in the Chinese population. Zhu et al 11 performed a meta-analysis containing 13 Chinese samples, 10 Caucasian samples and two samples from other populations. Stratified and combined analysis in the three different groups showed association of SNP rs1344706 with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%